Faktor-faktor yang Berhubungan dengan Tingkat Konsentrasi Belajar Mahasiswa Semester 1 Program Studi Pendidikan Ners STIKes Patria Husada Blitar - Erni Setiyorini (STIKes Patria Husada Blitar, 2016)
Students are individuals who take college-level education and have a basic need to learn. The learning process is successful if the learning objectives is achieved. One cause of low quality and learning achievement of individuals largely due to the weaknesses in learning to concentrate. The purpose of this study was: 1) to identify factors that affect the level of concentration of learning, 2) to identify the concentration levels of student learning 3) to analyze the factors relating the concentrations level of the first semester nursing students of STIKes Patria Husada Blitar. The research design used cross sectional design. The variables in this study were the factors that relate student learning concentration (environment, learning modalities, social and psychological) and the concentration level of learning. The population in this study was the first semester nursing students of STIKes Patria Husada Blitar. The whole population was used as the sample that was 23 people. The research was conducted on November 22nd, 2016. The data collected by a questionnaire. Data analysis used Chi -Square. The results showed that the factors relating the level of concentration of the first semester nursing students of STIKes Patria Husada Blitar was environmental factors (p = 0.001) and psychological factors (p = 0.008). The results of this research could be a baseline for future studies. For educational institutions, the results of this research could be used as an input to develop learning strategies to improve students’ concentration.